Enalikter is not an annelid: homology, autapomorphies and the interpretation of problematic fossils. (10th November 2016) - Parry, Luke A.; Legg, David A.; Sutton, Mark D.
Abstract : A megacheiran arthropod, Enalikter aphson, was recently described by Siveter et al . (2014) from the mid‐Silurian (late Wenlock) of Herefordshire. Previously, megacheirans had only been recognized from the Cambrian. Struck et al . (2015) considered the body plan of Enalikter to be incompatible with this affinity, arguing that many of the arthropod features were either not present or misinterpreted. Instead, they compared Enalikter to polychaete annelids, identifying characters from numerous polychaete lineages which they considered to be present in Enalikter . A reply to this critique by Siveter et al . (2015) reaffirmed arthropod affinities for Enalikter by presenting additional evidence for key arthropod features, such as arthropodized appendages. Here, we augment Siveter et al . by critically addressing the putative annelid characters of Enalikter presented by Struck et al . and additionally explore the morphological and phylogenetic implications of their hypothesis. We conclude that similarities between Enalikter and polychaetes are superficial and that character combinations proposed by Struck et al . are not present in any annelid, living or extinct. This taxon highlights the importance of using a phylogenetic framework for interpreting fossils that present unusual morphologies, such that proposed shared characters are hypotheses of homology rather than merely phenotypic similarities. Crucially, we argue that autapomorphic characters of subgroups of large taxa (like families or classes within phyla) should not be used to diagnose problematic fossils.